Americanah a novel - Chimamanda Ngozi Adichie (New York Alfred A. Knopf, 2013)
A young woman from Nigeria leaves behind her home and her first love to start a new life in America, only to find her dreams are not all she expected"-- Provided by publisher.
Keywords: Immigrants--Fiction. | Refugees--Fiction | Nigerians--United States--Fiction. | Nigerians--England--Fiction. Nigeria--Fiction.